The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1037/0735-7044.117.5.894
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal handling reduces the number of cells in the locus coeruleus of rats.

Abstract: Neonatal handling induces long-lasting effects on behaviors and stress responses. The objective of the present study was to analyze the effects of neonatal handling (from the 1st to the 10th day after delivery) on the number of cells and volume of locus coeruleus (LC) nucleus in male and female rats at 4 different ages: 11, 26, 35, and 90 days. Results showed significant reductions in the number of cells and the volume of the LC nucleus in neonatally handled males and females compared with nonhandled rats. Env… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 85 publications
(125 reference statements)
2
31
0
2
Order By: Relevance
“…Moreover, lesion of the LC in the morning of proestrus decreased the noradrenaline content in the MPOA and medial basal hypothalamus and blocked the preovulatory surge of LH and FSH and ovulation (Anselmo-Franci et al 1997). Previous studies showed that neonatal handling increases the expression of the adrenergic 2 inhibitory autoreceptors in the LC in male rats (Liu et al 2000) and induces a stable reduction in the number of cells in that noradrenergic nucleus in male and female rats (Lucion et al 2003). These changes in the LC could have diminished the stimulatory effect of LC on the hypothalamus and consequently reduced the LHRH surge in the proestrus afternoon.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, lesion of the LC in the morning of proestrus decreased the noradrenaline content in the MPOA and medial basal hypothalamus and blocked the preovulatory surge of LH and FSH and ovulation (Anselmo-Franci et al 1997). Previous studies showed that neonatal handling increases the expression of the adrenergic 2 inhibitory autoreceptors in the LC in male rats (Liu et al 2000) and induces a stable reduction in the number of cells in that noradrenergic nucleus in male and female rats (Lucion et al 2003). These changes in the LC could have diminished the stimulatory effect of LC on the hypothalamus and consequently reduced the LHRH surge in the proestrus afternoon.…”
Section: Discussionmentioning
confidence: 99%
“…This apparently harmless procedure in infancy reduces fear in novel environments (5-7) and the secretion of corticosterone, adrenocorticotrophin and prolactin in response to stressors in adulthood (4)(5)(6). Furthermore, preliminary results from our laboratory showed that neonatal manipulation reduced the number of neurons in the medial amygdala, the prefrontal cortex (8) and the locus coeruleus (9), and decreased the number of somatostatinergic neurons in the hypothalamic periventricular nucleus (10). These results suggest that neonatal handling can induce morphological changes in brain areas that could be the cause for the reduced stress responsiveness observed in adult animals.…”
mentioning
confidence: 88%
“…Handling increases pup vocalizations, which have, in turn, been associated with increased maternal licking. 38 Lucion et al, 39 Gomes et al, 40 Severino et al 41 and others were the first to demonstrate that neonatal stress alters reproductive mechanisms in the adult life. Lucion et al 39 demonstrated that neonatal handling reduces the number of cells in the locus coeruleus of rats in about 35%.…”
Section: Pre-clinical Studiesmentioning
confidence: 99%